2017
DOI: 10.1021/jacs.6b12817
|View full text |Cite
|
Sign up to set email alerts
|

Chain Folding Produces a Multilayered Morphology in a Precise Polymer: Simulations and Experiments

Abstract: Precise control over polymer architecture unlocks the potential for engineered self-assembled crystal structures with useful features on the nanometer length scale. Here we elucidate the structure of the ordered phase of a semicrystalline, functional polyethylene having a precise linear architecture, namely, pendant carboxylic acid groups precisely every 21st backbone carbon atom. By comparing the results of atomistic molecular dynamics simulations with experimental X-ray scattering and Raman spectroscopy data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 43 publications
8
72
0
Order By: Relevance
“…In bulk, polymer chains are rather folding according to a random reentry or the so-called "switchboard" model. 45,46 This model was first proposed by Flory and recently confirmed for a number of semi-crystalline polymers, 47 consists of chains randomly folding back into the same lamella or participating in adjoining lamellae. However, for solution-grown single monolayer polymer crystals, the most preferable chain-folding model is the adjacent reentry.…”
Section: Solid-state Characterizationmentioning
confidence: 92%
“…In bulk, polymer chains are rather folding according to a random reentry or the so-called "switchboard" model. 45,46 This model was first proposed by Flory and recently confirmed for a number of semi-crystalline polymers, 47 consists of chains randomly folding back into the same lamella or participating in adjoining lamellae. However, for solution-grown single monolayer polymer crystals, the most preferable chain-folding model is the adjacent reentry.…”
Section: Solid-state Characterizationmentioning
confidence: 92%
“…5). In contrast, the analogous carboxyl-containing polyethylene (p21AA) does exhibit a long period peak 8, 9 . Applying the Scherrer equation to the primary sulfonic layer peak yields a minimum crystal size of ~700 Å along the vector normal to the layers.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Control of chain folding and morphology ismade possible by precise control of the chain microstructure via acyclic diene metathesis synthesis 5,8,31-34 . Our previous work showed that periodic placement of pendant atactic carboxyl groups along linear polyethylene produces controlled chain folding and layers of acid groups 9 . Here, sulfonic acid groups 35 , which are highly hygroscopic moieties, replace carboxyl groups, producing hydrated layers with high proton conductivity.…”
mentioning
confidence: 99%
“…Recently, in a DFT study including dispersion corrections, the slip mechanisms and ground state twin configurations in crystalline orthorhombic PE were assessed to accurately characterize PE crystal defects and plasticity mechanisms [264]. Winey et al [265] reported that the polymer chains are folded in different ways depending on the type of branching. Non polar functional groups are excluded from the crystal, which spans only the crystallisable ethylene sequence between the branches [266].…”
Section: The Orthorhombic Unit Cellmentioning
confidence: 99%